A (in)tangibilidade da coisa julgada perante decisão de inconstitucionalidade : uma análise do parágrafo 15 do artigo 525 do Código de Processo Civil - Lyra, João Paulo Barbosa (2017)
The main goal of this dissertation is to analyze the compatibility of paragraph 15 of Article 525 of the Code of Civil Procedure with the Brazilian Legal Order. From the theoretical model of logico-semantic constructivism, Law is understood as a set of rule of laws and cultural object constituent by its own realities by means of deontic speech act. To each production of legal norm there is a new legal system in a certain time. Legal security safeguards legal facts that occur in each of the legal system , ensuring the maintenance of the legal relationships created by Law. In order to protect the Federal Constitution, the constituent created forms of constitutionality control which will be proceeded either in a diffuse way, or in a concentrated way, not having hierarch between these two forms. From this perspective, the concept of res judicata is set from its normative structure as well as fundamental right guaranteed by the Federal Constitution of 1988. This theoretical and legislative panorama support the conclusion by the unconstitutionality of the provision in the Code of Civil Procedure of 2015.